Practical aspects of declarative languages : 21th International Symposium, PADL 2019, Lisbon, Portugal, January 14-15, 2019, Proceedings /: 21th International Symposium, PADL 2019, Lisbon, Portugal, January 14-15, 2019, Proceedings. (2019) - Unknown
No abstract available